Exploring Community-Dwelling Older Adults' Considerations About Values and Preferences for Future End-of-Life Care: A Study from Sweden. (21st March 2020) - Eneslätt, Malin; Helgesson, Gert; Tishelman, Carol
Abstract: Background and Objectives: There is a substantial body of research on advance care planning (ACP), often originating from English-speaking countries and focused on health care settings. However, studies of content of ACP conversations in community settings remain scarce. We therefore explore community-dwelling, older adults' reasoning about end-of-life (EoL) values and preferences in ACP conversations. Research Design and Methods: In this participatory action research project, planned and conducted in collaboration with national community-based organizations, we interviewed 65 older adults without known EoL care needs, about their values and preferences for future EoL care. Conversations were stimulated by sorting and ranking statements in a Swedish version of GoWish cards, called the DöBra cards, and verbatim transcripts were analyzed inductively. Results: While participants shared some common preferences about EoL care, there was great variation among individuals in how they reasoned. Although EoL preferences and prioritizations could be identical, different individuals explained these choices very differently. We exemplify this variation using data from four participants who discussed their respective EoL preferences by focusing on either physical, social, existential, or practical implications. Discussion and Implications: A previously undocumented benefit of the GoWish/DöBra cards is how the flexibility of the card statements support substantial discussion of an individual's EoL preferences and underlying values. Such in-depth descriptions of participants' reasoning and considerations are important for understanding the very individual nature of prioritizing EoL preferences. We suggest future users of the DöBra/GoWish cards consider the underlying reasoning of individuals' prioritizations to strengthen person-centeredness in EoL conversations and care provision.